Pentahelix-Based Stakeholder Governance Model at the Tugu Khatulistiwa in Pontianak City - Tandri, Stella (SABA: Journal of Tourism Research, 2024)
The Tugu Khatulistiwa is an icon of Pontianak City which functions as a tourism attraction that stores historical value and becomes a cultural heritage site. The development of the Tugu Khatulistiwa as tourist attraction had experienced obstacles due to land ownership problems which have now been successfully resolved. The development of the Tugu Khatulistiwa is not only the responsibility of the Pontianak City Tourism Agency Office (Disporapar) as the manager but must involve other stakeholders in accordance with their roles and interests. This study aims to identify the stakeholders of the Tugu Khatulistiwa, analyze their interests and influence, and determine the governance model for the Tugu Khatulistiwa stakeholders. By using a qualitative approach this research seeks to explore the phenomenon of stakeholders and present it descriptively. Data were analyzed using stakeholder analysis techniques. The researcher succeeded in identifying as many as 36 interviewees of the Tugu Khatulistiwa’s stakeholder with 30 interviewees spread out in the key players quadrant in the interest and influence matrix. Researchers have also created actor-linkage matrices that help determine the final results of the research which is a model for stakeholder governance at the Tugu Khatulistiwa in the form of collaboration. There are 13 groups/organizations who play important roles based on their respective fields. At the end, the researcher suggests further research on stakeholder collaboration which is discussed more technically, making it easier for stakeholders to implement directly.